Cheng Dieyi in Farewell My Concubine, A drag or an act? A queer or an actor? - Hongru, Xing (Sinología hispánica. China Studies Review, 2022)
This article reflects on the character Cheng Dieyi, highlighting the gender trouble that emerges through the corporality. From Judith Butler’s theory of gender performativity, the article attempts to propose the possible connection between the drastic shift in Dieyi’s gender identity and the repetitive and performative practices of female impersonation throughout his professional learning to be a male Dan* actor of the Beijing Opera (Jingju). Beyond a usual reading which attributes Dieyi’s suicide to psychological disorders that confuse life and performance, my hypothesis is that his gender trouble should be understood as queerness in affective and intimate terms; thus, exposes the dynamic relation between performance and performativity and invites reflections and criticisms about such dynamics in Butlerian performativity.